Who rides on the river? - Ewers, John K. (John Keith), 1904-1978.; Durack, Elizabeth, 1915-2000. (Sydney : Angus and Robertson, 1956)
Fictionalized account of Charles Sturt's journey down the Murrumbidgee and Murray Rivers and back again.
Muir, M. A bibliography of Australian children's books
For children.
Keywords: Sturt, Charles, -- 1795-1869 -- Travel -- Australia, Southeastern -- Juvenile fiction; Settlement and contacts - Explorers; Literature and stories - Juvenile; Murray River (N.S.W.-S.A.) -- Discovery and exploration -- Juvenile fiction; Murrumbidgee River (N.S.W. and A.C.T.) -- Discovery and exploration -- Juvenile fiction; Southwest New South Wales (SW NSW SI54, SI55); Sydney (NSW SI56-05); River Murray (SW NSW, N Vic, SE SA SI54, SI55); North West Victoria (NW Vic SI55); Children's stories, Australian; Historical fiction